TEACHING WRITING A DESCRIPTIVE TEXT BY USING GUIDED WRITING STRATEGY - Asep Sumarna; Rissa San Rizqiya (IKIP Siliwangi, 2023)
Most of the students' problem in writing is that they do not know how to develop ideas in writing. They write based on what is in their mind randomly without any technique that can help them to write ideas directly, because they use limited thinking skills to solve a problem. The guided writing strategy technique was applied to improve students' skills in writing descriptive texts. To apply this technique, a pre-experimental research was conducted at SMK Islam Solalatul Huda, with a population of class X ADM students and a research sample of 38 students. To obtain data showing the effect of the technique, pre-test and post-test were used as instruments, and tests were used as a data collection tool. Based on the results of hypothesis testing and analysis, it is shown that teaching writing descriptive texts has a strong influence on teaching writing descriptive texts at SMK Islam Solalatul Huda. Therefore, this technique is recommended to be applied in teaching writing descriptive text.